Strain localization and elastic-plastic coupling during deformation of porous sandstone. (October 2017) - Dewers, Thomas A.; Issen, Kathleen A.; Holcomb, David J.; Olsson, William A.; Ingraham, Mathew D.
Abstract: Results of axisymmetric compression tests on weak, porous Castlegate Sandstone (Cretaceous, Utah, USA), covering a range of dilational and compactional behaviors, are examined for localization behavior. Assuming isotropy, bulk and shear moduli evolve as increasing functions of mean stress and Mises equivalent shear stress respectively, and as decreasing functions of work-conjugate plastic strains. Acoustic emissions events located during testing show onset of localization and permit calculation of observed shear and low-angle compaction localization zones, or bands, as localization commences. Total strain measured experimentally partitions into: A) elastic strain with constant moduli, B) elastic strain due to stress dependence of moduli, C) elastic strain due to moduli degradation with increasing plastic strain, and D) plastic strain. The third term is the elastic-plastic coupling strain, and though often ignored, contributes significantly to pre-failure total strain for brittle and transitional tests. Constitutive parameters and localization predictions derived from experiments are compared to theoretical predictions. In the brittle regime, predictions of band angles (angle between band normal and maximum compression) demonstrate good agreement with observed shear band angles. Compaction localization was observed in the transitional regime in between shear localization and spatially pervasive compaction, over a small range of mean stresses. In contrast with predictions, detailed acoustic emissions analyses in this regime show low angle, compaction-dominated but shear-enhanced, localization. Highlights: New experimental data for sandstone deformation is presented, covering a range in stress space and localization behavior. Locations of acoustic emissions events were used to identify modes of strain localization. Degradation of elastic moduli with accumulating plastic strain has a major influence on overall deformation response. Total strain was partitioned into three components of elastic strain, and plastic strain, for constitutive modeling. Rudnicki and Rice 44 constitutive framework is used for localization and band angle predictions. Theory shows a reasonable predictive agreement for the experimental results, once moduli degradation is taken into account.